Impact of Contrasted Weather Conditions on CDOM Absorption/Fluorescence and Biogeochemistry in the Eastern Lagoon of New Caledonia - Dupouy, Cécile; Röttgers, Rüdiger; Tedetti, Marc; Frouin, Robert; Lantoine, François; Rodier, Martine; Martias, Chloe; Goutx, Madeleine (Frontiers in Earth Science, 2020)
New Caledonia (Southwest Pacific), like all tropical Pacific Island countries, is impacted by weather events, climate change, and local anthropogenic forcing. Strong erosion of particles and dissolved organic matter (DOM) from ultramafic rocks, associated with trace metals dissemination (i.e., nickel, manganese and cobalt), potentially affects lagoon waters and coral reefs surrounding the main island. The CALIOPE (CALedonian Inherent Optical PropErties) cruises were performed along the Eastern Lagoon of New Caledonia (ELNC) (400 km, 13 transects from Bay to open ocean, 51 stations) during contrasted meteorological conditions: a dry period (October 2011), a windy situation (March 2014), and a strong rainy event (March 2016). CDOM absorption and fluorescence (FDOM), particulate absorption, backscattering, suspended particulate matter (SPM), total chlorophyll a (TChla), nutrients (NOx), pigment and phytoplankton composition were measured. Among the four CDOM fluorophores, the humic-like component (λEx/λEm: 235/460 nm), assimilated to a photoproduct of terrestrial organic matter, had relatively low fluorescence compared to protein-like fluorophores. As CDOM absorption, particulate absorption, backscattering, suspended particulate matter (SPM), total chlorophyll a (TChla) and nutrient (NOx) concentrations, this humic-like material generally showed the highest values during rainfall events, the latter inducing an increase in riverine terrigeneous inputs and change towards higher phytoplankton size classes. The tyrosine 1-like (λEx/λEm: 220, 275/304 nm) and tryptophan-like fluorophores (λEx/λEm: 230, 300/352 nm) were strongly influenced by wind displaying a 7-fold and 3-fold increase, respectively in windy situation compared to calm conditions. These increases could be related to enhancements of autochthonous biological activities (highest mean concentrations of Synechococcus spp., phycoerythrin, pico- and nano-eukaryotes, heterotrophic bacteria and nanoplankton observed in wind condition) through the inputs of organic and mineral materials issued from the wind-induced sediment resuspension, atmospheric deposition and water mass mixing. By contrast, the tyrosine 2-like fluorophore (λEx/λEm: 245, 275/304 nm) substantially increased during rain events and presented the lowest values in wind conditions. These strong increases may be linked to the stimulation of planktonic activities due to riverine inputs. Therefore, this study emphasizes the significant differential influence of weather conditions (calm/wind/rain) on biogeochemistry and CDOM/FDOM distributions in the ELNC.